The Pedagogical Encouragement of Self-Regulation Applying PMM during the Activities (Proceedings of the International Conference on Education, 2020)
Performing for an audience is one of the most widely spread forms of social anxietywhich affects many people, and fear is one of the most important causes of unsuccessfulperformance on stage. A university student – a future music teacher – experiences what it is likebeing in front of an audience and to feeling emotional strain. The aim of this research is to explorethe ways which encourage students to feel better in front of an audience. Is it possible to overcomesignificant stage fright by having knowledge of psychological self-regulation? This article disclosesthe modelling of concert rehearsal tasks during individual lessons applying the personal meaningmethod (PMM): creating favourable preconditions to optimize the state of mind while on stage;strengthening the artistic suggestion of public performance of future teachers; positively influencingthe learning motivation of students. Observation helped to analyze more deeply the behaviour ofstudents and their activity in the process of training, comparing these dimensions with respectivechanges during public performances. PMM training verifying case method of analysis in the contextof possibilities revealed the conditions of future music teachers’ regulation of emotions while onstage, ways and the peculiarities of pedagogical encouragement.
Keywords: pedagogical encouragement; self-regulation; PMM